Cobalt-catalyzed directed alkylation of olefinic C-H bond with primary and secondary alkyl chlorides - Yamakawa, Takeshi (2015)
A cobalt–N-heterocyclic carbene catalytic system promotes pyridine-directed olefinic C–H alkylation reactions using a variety of primary and secondary alkyl chlorides under mild conditions. Radical clock experiments suggest that the reaction involves single-electron transfer from the cobalt intermediate to the alkyl chloride.